The Development of Collaborative Marketing Website for Digital Learning Materials - Triyanna Widiyaningtyas; Aji Prasetya Wibawa; Utomo Pujianto (Jurnal Pendidikan Sains, 2018)
Abstract: Website is a collection of related pages and used to display information in the form of text, images, sounds, or a combination of everything that is static or dynamic. Website can be used as a marketing tool. This article discusses collaborative website development for marketing digital teaching materials. The development of this website is expected to increase the usefulness of student thesis products in the form of teaching materials. Finally this development study finds that the website can be implemented for selling the academics products.Key Words: collaborative marketing, website, digital learning materialsAbstrak: Website adalah kumpulan halaman terkait dan digunakan untuk menampilkan informasi dalam bentuk teks, gambar, suara, atau kombinasi dari segala sesuatu yang statis atau dinamis. Website dapat digunakan sebagai alat pemasaran. Artikel ini membahas pengembangan website kolaboratif untuk pemasaran materi pengajaran digital. Pengembangan website ini diharapkan dapat meningkatkan kegunaan produk tesis mahasiswa dalam bentuk bahan ajar. Akhirnya studi pengembangan ini menemukan bahwa website dapat diimplementasikan untuk menjual produk akademik. Kata kunci: pemasaran kolaboratif, laman, materi pembelajaran digital